2019
DOI: 10.1152/ajpcell.00345.2018
|View full text |Cite
|
Sign up to set email alerts
|

Neurogranin is expressed in mammalian skeletal muscle and inhibits calcineurin signaling and myoblast fusion

Abstract: Calcineurin is a Ca2+/calmodulin (CaM)-dependent phosphatase that plays a critical role in promoting the slow fiber phenotype and myoblast fusion in skeletal muscle, thereby making calcineurin an attractive cellular target for enhancing fatigue resistance, muscle metabolism, and muscle repair. Neurogranin (Ng) is a CaM-binding protein thought to be expressed solely in brain and neurons, where it inhibits calcineurin signaling by sequestering CaM, thus lowering its cellular availability. Here, we demonstrate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 63 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…Together, these findings would suggest that Ng has a negative role in CaM activation. Ng was once thought to be a neuronal specific protein; however, we have recently discovered that Ng is expressed in mammalian skeletal muscle (rodent and human), and is particularly abundant in slow-oxidative muscle fibers [28]. Using C2C12 cells, our results showed that silencing Ng increased CaM-CaN binding-indicative of a role for Ng in sequestering CaM in these muscle cells.…”
Section: Neurograninmentioning
confidence: 65%
See 4 more Smart Citations
“…Together, these findings would suggest that Ng has a negative role in CaM activation. Ng was once thought to be a neuronal specific protein; however, we have recently discovered that Ng is expressed in mammalian skeletal muscle (rodent and human), and is particularly abundant in slow-oxidative muscle fibers [28]. Using C2C12 cells, our results showed that silencing Ng increased CaM-CaN binding-indicative of a role for Ng in sequestering CaM in these muscle cells.…”
Section: Neurograninmentioning
confidence: 65%
“…Though neither CaN or CaMKII activation have been directly examined in muscles from Gap43-null mice, Caprara et al [45] did not observe any effects of Gap43 deletion (heterozygous or homozygous) on myoblast fusion and differentiation in primary myoblasts. Given the role of CaN in regulating myoblast fusion and myogenic differentiation [27,28], these results suggest that GAP43 may have less of a role in regulating CaN and is rather more important in regulating free intracellular Ca 2+ during muscle contraction and relaxation. Future studies that examine whether genetic deletion of Gap43 alters fibre type distribution and fatigue resistance, similar to that conducted with Nrip-null mice [9], will provide more insight towards the role of GAP43 in regulating CaM activation of CaN and CaMKII.…”
Section: Growth-associated Protein 43mentioning
confidence: 96%
See 3 more Smart Citations